Feed Additives Differentially Impact the Epimural Microbiota and Host Epithelial Gene Expression of the Bovine Rumen Fed Diets Rich in Concentrates - Petri, Renee Maxine; Neubauer, Viktoria; Humer, Elke; Kröger, Iris; Reisinger, Nicole; Zebeli, Qendrim (Frontiers in Microbiology, 2020)
The success of nutritional strategies for the prevention of subacute ruminal acidosis (SARA) and the related microbial dysbiosis still remains unpredictable due to the complexity of the rumen ecosystem. The rumen epimural community, due to proximity, has the greatest opportunity to influence host gene expression. The aim of this study was to determine the effect of two separate feed additives on the rumen epimural community and host epithelial gene expression. Eight rumen cannulated Holstein cows were randomly assigned to one of three feeding groups: autolyzed yeast (AY), phytogenics (PHY) and control (CON) using a 3 × 3 Latin square design. Cows were fed an intermittent SARA model that started with 100% forage diet (Baseline) followed by two 65% concentrate-diet induced SARA challenges (SARAI, SARAII), separated by 1 week of forage only feeding. Rumen papillae samples were collected via the cannula during the Baseline, SARAI and SARAII periods. Microbial DNA was extracted and sequenced targeting the 16S rRNA gene and host RNA was analyzed using RT-qPCR. Analysis of the taxonomic composition at the genera level showed a tendency to increase in the relative abundances of Pseudobutyrivibrio (P = 0.06), Selenomonas (P = 0.07) and significantly increase in SHD-231 (P = 0.01) in PHY treated animals, whereas Succiniclasticum tended to decrease in both PHY and AY treated animals compared to the control. Linear discriminant analysis effect size testing was performed and based on treatment × feeding phase interaction, a number of biomarker genera were identified including the previously identified Succiniclasticum. Supplementation with AY correlated positively with CD14 and DRA expression and negatively to CLDN1, MyD88, and MCT4 expression. Supplementation with PHY showed a negative correlation to CLDN4 gene expression. Anaerovibrio showed the highest positive Pearson correlations to biogenic amines tested in the rumen fluid including putrescine (r = 0.67), cadaverine (r = 0.84), and tyramine (r = 0.83). These results show that supplementing feed additives to high grain diets can have a positive influence on the stability of the epimural populations, and that changes in the epimural community are correlated with changes in host epithelial gene expression.